Education as and for Legitimacy : Developments in West Indian Education Between 1846 and 1895. - Bacchus, M. Kazim (Wilfrid Laurier University Press, 2006)
This study of the development of education in the British West Indian colonies during the last half of the nineteenth century examines the educational policies and curriculum used in schools following the abolition of slavery. During this period the nature and development of the educational system in the region was profoundly affected by the decline of the sugar industry, the emergence of black and coloured middle classes and the threat they posed to the ruling white elite, and the institutionalization of cultural divisions between the black and white populations. Bacchus argues that after 18.